Antimicrobial Resistance and Its Control Policy Implementation in Hospital in Indonesia - Handayani, Rini Sasanti; Siahaan, Selma; Herman, Max Joseph (Pusat Penelitian dan Pengembangan Sumber Daya dan Pelayanan Kesehatan, 2017)
Antimicrobial Resistance (AMR) is a serious issue because it may reduce treatment effectiveness, increase infection transmission and health care costs. This article aims to identify the problems and the implementation of the AMR control program in hospital. Method :Data were collected by reviewing study results in journals and proceedings, books/literature on AMR at universities and hospitals in Jakarta and Bandung, regulation on the distribution and use of antimicrobials at NADFC, control policy on AMR of MoH RI, as well as data of nosocomial infections from National Survey on Health Facility (Rifaskes 2011). We also conducted consensus decision making which discusses strategic plan and policy for controlling AMR as well as how to optimize or strengthen the strategy with participants involving type Ahospital AMR Control Committee as keynote speakersandDirectorateof ReferralHealth Services, Directorateof Health Service Facility, Directorateof Pharmacy Services, Private and Public Hospital Directors in DKI Jakarta, Hospital Accreditation Commission (KARS), others researchers and academicians as stake holders.In Indonesia AMR control program has been started in some hospitals, but there are still many obstacles either from the management, facilities or infrastructures and practitioners. The policies related to AMR control in Indonesia are stated in Law No. 36 of 2009, Law No. 44 of 2009 and the Ministry of Health Decree No. 8 of 2015. There is also a guideline of the Ministry of Health forInfectionControlPrograminhospital. These policiesshouldbeimplementedandusedasatoolto increase the commitment of the hospital management. Compliance with the guidelines should be strictly implemented, besides the rational prescription of antimicrobials, completing facilities and infrastructures for controllingAMR and the establishment of surveillance of antibiotic use.